2016
DOI: 10.1038/srep28286
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in Traditional Korean Medicine: A Nine-Year Multicentre Community-Based Study in South Korea

Abstract: In Korea, patients with stroke are commonly treated using traditional Korean medicine (TKM). The aim of this study was to provide information on the clinical characteristics of the pattern identification (PI) of stroke used in TKM. Stroke patients admitted to 15 TKM university hospitals from April 2005 through December 2013 were evaluated. The measured variables included the following factors as they related to the PI: (a) stroke etiology; (b) distribution of symptoms/signs; (c) physical characteristics and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…us function of gathering Qi is closely related to the whole body condition and more closely to circulation and respiratory function, as Zhang Xichun said "gathering Qi actually controls general health while remains in cheat." Like Qi deficiency, when there is insufficient of Zong Qi, we often show symptoms such as fatigue and shortness of breath, which leads to decreased activity tolerance [2,43]. With the development of modern medicine, we found that the function of Zong Qi is related to the respiratory system, circulatory system, nervous system, and even reproductive system.…”
Section: Evidence-based Complementary and Alternative Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…us function of gathering Qi is closely related to the whole body condition and more closely to circulation and respiratory function, as Zhang Xichun said "gathering Qi actually controls general health while remains in cheat." Like Qi deficiency, when there is insufficient of Zong Qi, we often show symptoms such as fatigue and shortness of breath, which leads to decreased activity tolerance [2,43]. With the development of modern medicine, we found that the function of Zong Qi is related to the respiratory system, circulatory system, nervous system, and even reproductive system.…”
Section: Evidence-based Complementary and Alternative Medicinementioning
confidence: 99%
“…Qi deficiency causes pale face, shortness of breath, weakness of limbs, dizziness, diarrhea, and other symptoms. Qi deficiency is associated with a variety of diseases, especially cardiovascular and cerebrovascular diseases [1,2]. According to the guidance of TCM, the use of Atractylodes macrocephala, Astragalus, and even medical qigong has played a therapeutic effect on many diseases caused by Qi deficiency [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…There is an estimated 33 million people with stroke, many of whom suffer from stroke-related disability [2]. In Korea, the second most common cause of death is stroke, and the treatment and management of stroke incur a large financial burden [3].…”
Section: Introductionmentioning
confidence: 99%